Analysis of CoDBR and CEEDBR protocols in underwater wireless sensor networks - S. Rajini; M. Ramakrishna (BOHR Journal of Computational Intelligence and Communication Network, 2023)
Underwater wireless sensor networks (UWSNs) are essential for doing any type of task underwater. Huge broadcast lag, great error degree, small bandwidth, and restricted energy in Underwater Sensor Networks interest concentration of utmost investigators. In UWSNs, the efficient use of energy is one of the main problems, as the substitution of energy sources in this kind of location is extremely costly. UWSNs are utilized in many fields, like measuring pollution, issuing tsunami cautions, conducting offshore surveys, and strategic tracing. For numerous functions, the efficacy and dependability of network regarding prominent operation, energy preservation, small bit error rate, and decreased interruption are fundamental. Nevertheless, UWSN’s exclusive features like small bandwidth accessibility, large interruptions in broadcast, very vivacious network topology, and extreme possibility of error present numerous problems in the growth of effective and dependable communication procedures. As opposed to current deepness-based routing techniques, we are focusing on CoDBR (Cooperative Depthbased Routing) and CEEDBR (Cooperative Energy Efficient Depth-based Routing) procedures to improve network lifespan, energy efficacy, and amount.